Government policy statements related to rice problems in Indonesia: Review - Nico Harro Silalahi; Rizdha Okkianty Yudha; Evita Izza Dwiyanti; Desiana Zulvianita; Salsabilla Nur Feranti; Yooce Yustiana (3BIO: Journal of Biological Science, Technology and Management, 2019)
Rice policy is an important element in food security. In its control, the government regulates food management through Logistics Affairs Agency of Indonesia (Bulog). This research aimed to examine government policy related to rice problem in Indonesia using descriptive qualitative analysis method through literature study. The policy of fulfillment of rice needs in Indonesia has been done since the beginning of independence until now. The high demand of the Indonesian people on rice commodities caused fluctuations in rice availability which had an impact on the unstable price, plus the unavailability of enough land to increase domestic rice productivity. Rice import activities are being undertaken from several neighboring countries to address the problem, with the largest number of imports occurring in 2011 over the last 15 years, and the least imports occurring in 2005. The government through Bulog controls the stability of rice stocks and prices for producers through basic price instruments, marketing, rice distribution (post-production), and the supply of staples at the consumer level. In addition, the government through the Community Food Business Development (PUPM) launched the Indonesian Farmer Shop (TTI) program that sells foodstuffs, including rice, at low prices. This program is created as a form of solution to the high price of food demand in Indonesia as a result of the length of the supply chain so the food supply system becomes inefficient. The government has also set the highest retail price policy (HET) and cost of goods sold (HPP) as an effort to stabilize the price of major food commodities in Indonesia, including rice. In the application of HET and HPP values have undergone some changes but still can not achieve price stabilization and improve the economy of farmers, especially small farmers. It is advisable that government policies related to HET and HPP through the Regulation of the Minister of Trade should pay attention for actual price fluctuations and should be distinguished based on the quality of rice, so that price stabilization and the desire to promote farmers in Indonesia can be realized.